Individual’s Resistance Regarding BPM Initiative: Case Study of the Insurance Company - Pejić Bach, Mirjana; Bosilj Vukšić, vesna; Suša Vugec, Dalia (Naše gospodarstvo/Our economy, 2017)
Though the individual’s resistance is very often considered a significant barrier to BPM success, the literature on that topic is quite scarce. With the aim to shed light on this topic, we have conducted research of a Croatian insurance company. We examined the impact of individual’s resistance regarding BPM initiative using the theory of reasoned action. Structural equation model was developed using the data collected by the survey among company employees. The results indicate that subjective norms are positively related to the individual’s resistance regarding BPM initiative, while positive initial belief regarding BPM initiative tends to decrease the probability of resistance to change.
Keywords: business process management; theory of reasoned action; individual’s resistance; insurance company; change management; Croatia